Total Physical Response (Tpr) In Teaching Vocabulary To Slow Learners: A Phenomenological Study Of Seventh Grade Teachers - Raudhotu Fadhilah; Farida Repelita Waty Br Kembaren; Yani Lubis (EXCELLENCE: Journal of English and English Education, 2026)
This study aimed to explore the experience of an English teacher in implementing the Total Physical Response (TPR) method to enhance vocabulary mastery for slow learners in a seventh-grade inclusive class at SMP Muhammadiyah Medan. The research background arises from the need to find effective teaching strategies for slow learners who face challenges with traditional learning methods. The study employed a narrative inquiry approach, involving one primary teacher participant and one supporting slow learner student. Data were collected through narrative interviews, classroom observations, reflective notes, and supporting documentation, then analyzed using *transcription, restorying, and thematic coding.The findings indicate that TPR significantly improves students’ ability to understand, retain, and use vocabulary by linking words with physical movements. Slow learners showed increased confidence, active participation, and better vocabulary retention after engaging in TPR-based lessons. TPR also fosters a more inclusive and interactive classroom environment. Teacher strategies such as repeated instructions, breaking lessons into simpler steps, and direct demonstration proved effective in supporting slow learners’ learning process. Based on these findings, it is recommended that teachers consistently apply TPR, students actively participate in movement-based activities, schools support active learning strategies, and future researchers explore the integration of TPR with other teaching methods in inclusive classroom contexts.